The Relationship between Serum Trace Elements and Oxidative Stress of Patients with Different Types of Cancer - Yang, Yu-wei; Dai, Chun-mei; Chen, Xiao-hong; Feng, Jia-fu (Oxidative medicine and cellular longevity, 2021)
Objective. Many studies have identified causal and promotive roles of oxidative stress (OxS) and oxidative damage caused by OxS in the occurrence and progression of cancer. Many biomarkers in the blood circulation of patients may change correspondingly with the development of tumors. This study is aimed at investigating the correlation between OxS and serum trace element (TE) levels of patients with different types of cancer. Methods. 1143 different types of cancer patients and 178 healthy controls from Mar. 2018 to Aug. 2020 in Mianyang Central Hospital were involved in this study. Their levels of OxS parameters (including total oxidant status (TOS), total antioxidant status (TAS), and oxidant stress index (OSI)) and the concentrations of serum TEs (including Cu, Zn, Fe, and Se) were determined. Results. Compared with healthy controls, all types of cancer patients had higher TOS level (all Padj<0.001) and OSI level (z=6.228~9.909, all Padj<0.001) and lower TAS level (all Padj<0.001). Compared with healthy controls, the changes of four TE levels in serum were different in different types of cancer patients, among which Cu increased in all groups, but there was no statistical difference in gastric and brain cancer; Se decreased in all groups, but there was no statistical difference in gastric, colorectal, esophageal, and other cancer; Zn was significantly decreased in breast cancer patients (Padj<0.001); there was no statistical difference in the change of Fe in liver, kidney, and other cancer. Spearman correlation showed that the change of Cu concentration was most closely related to the three OxS parameters and was strongly correlated in the observed several types of tumors (rs>0.6). Multinomial logistic regression showed that the risks of different tumors are related to the level change of multiple TEs and OxS parameters (ORTOS=1.19~2.82, OROSI=2.56~4.70, ORTAS=0.20~0.46, ORCu=0.73~1.44, ORZn=0.81~0.91, ORFe=0.68~1.18, and ORSe=0.22~0.45, all P<0.006). Conclusions. The OxS exists in the occurrence and development of cancer, which may be related to the changes of certain trace elements. In order to evaluate OxS correctly, it is necessary to detect TAS and TOS and at the same time, their ratio OSI should be detected. Assessment of markers representing the overall level of OxS and TEs may guarantee improved the monitoring of disease occurrence and development risk in cancer patients.